Schwann cells promote the migration and invasion of colorectal cancer cells via the activated NF-κB/IL-8 axis in the tumor microenvironment - Chen, Shuhai; Chen, Mingyou (Frontiers in Oncology, 2022)
Background: Evidence has shown neurons and glial cells were closely related to tumor progression. As the predominant glial cells in the external innervated nerves of the gastrointestinal, the role of Schwann cells (SCs) in colorectal cancer (CRC) has not been well explored. Methods: HCT-116 and HT-29 CRC cells were treated with conditioned medium (CM) from SCs, and the cells’ proliferative and migrating capacities were examined. Cytokine array analysis was used to identify the tumor-promoting-cytokines from SCs-CM. Molecular changes from SCs after being co-cultured with tumor cells were detected by ELISA and reverse transcription-quantitative PCR. The activation of the nuclear factor kappa B (NF-κB) signaling pathway in SCs was demonstrated by immunofluorescence staining. Neutralizing antibody was used to verify the tumor-promoting effects of key cytokine. Results: Migration and invasion of CRC cells were markedly aided by CM from SCs in vitro. Interleukin-8 (IL-8) was identified as an effective factor. SCs co-cultured with CRC cells upregulated IL-8 expression, which may be related to its activated NF-κB signaling pathway. Neutralization of IL-8 attenuated the tumor-promoting effect of SCs. Conclusion: The present study identified a new mechanism of tumor-neuroglia interaction, enriching the concept of the tumor-neural axis in the tumor microenvironment of CRC, which also inspired potential targets for anti-cancer therapies.